Clinical manual of couples and family therapy - Keitner, Gabor I. 1947- (IG library, 2010)
The Clinical Manual of Couples and Family Therapy outlines practical, evidence-based family therapy skills, and it also reestablishes the role of the psychiatrist as the leader of the team of professionals providing mental health care to patients in need.